Allometry, condition factor and growth of the swimming blue crab Portunus segnis in the Gulf of Gabes, Southeastern Tunisia (Central Mediterranean) - BEN ABDALLAH-BEN HADJ HAMIDA, OLFA; BEN HADJ HAMIDA, NADER; CHAOUCH, HOUDA; MISSAOUI, HECHMI (Mediterranean Marine Science, 2019)
The blue swimming crab Portunus segnis (Forskål, 1775) is one of the earliest Lessepsian invaders of the Mediterranean Sea, and is recorded since decades in various areas of the Mediterranean. Its presence in the southeastern Tunisian coasts (Gulf of Gabes) is, however, very recent. Allometry, condition factor and growth of P. segnis were studied along the Gulf of Gabes coasts. Sampling was performed by artisanal fishing gears as well as trawl net during a one-year period (October 2015 to September 2016) as processed 4971 crabs were collected. The crab carapace width (CW) ranged from 45 to 168 mm for males and 50 to 159 mm for females. The crab carapace length (CL) was 22.02-89.20 mm and 38.70-85.28 mm, respectively for males and females. The carapace width-carapace length, carapace width- front, carapace width-carapace height and carapace width-weight relationships were studied in separate sexes of crab. The covariance analysis indicates a significant difference between the two sexes with respect to the carapace width-carapace length and the carapace width-weight relationships. The condition factor ranged between 0.0042 and 0.0118 with a mean of 0.0078. The condition factor decreased with increasing crab size. The Von Bertalanffy growth parameters CW∞, K and t0 were estimated on the basis of Length-frequency modal progression analysis methods. The mean values of L∞ (mm), K (year-1) and t0 would be, respectively, 206.48 mm, 1.34 and -0.130 for males; 183.89 mm, 1.42 and -0.127 for females and, 190.60 mm, 1.02 and -0.177 for combined sexes.